Application of The Physics Aviary Virtual Laboratory to Support Student Motivation and Self-Regulated Learning - Nurlina Nurlina; Nur Aisyah Humairah; Ummu Kalsum; Fauziah. A; Maisarah Maisarah; Widia Widia; Wita Fardilla (Universitas Nurul Jadid, 2025)
Limited access to adequate physics laboratory facilities remains a major challenge in Indonesian schools, including SMAN 1 Mamasa, where conventional physics learning often lacks hands-on experiments. To address this issue, this study was conducted as part of a Community Service (PkM) activity, providing training and mentoring on the use of The Physics Aviary (TPA) virtual laboratory for eleventh-grade students. The activity employed Community-Based Research (CBR) and Service Learning approaches, enabling students to actively participate in meaningful learning experiences while contributing to the community. A total of 34 students (20 females, 14 males) participated in the program, which was conducted from July to August 2025. Data on learning motivation and self-regulated learning (SRL) were collected using validated questionnaires and analyzed descriptively. The results indicate that the virtual laboratory effectively fostered students’ intrinsic motivation, with the highest scores observed in intrinsic goal orientation (mean = 4.12, SD = 0.95) and task value (mean = 4.06, SD = 0.89). Additionally, SRL skills were reflected in high scores for time and study environment management (mean = 4.06, SD = 0.81) and peer learning (mean = 3.91, SD = 0.99). Student satisfaction with the training was also high, demonstrating successful implementation. This PkM activity not only introduced TPA in the local school context but also provided initial empirical evidence that virtual labs can serve as effective alternatives for fostering motivation and self-regulation in secondary physics education. However, the findings highlight the need to strengthen metacognitive and collaborative learning aspects.